Use of Concept Map Media with Integrated Adlx-Based Learning Design to Improve Student Learning Outcomes in Class X Biotechnology Material IT Ummul Quro Bogor Semester Even Semester 2023-2024 Academic Year - Haris Sandi Novaldo; Rahma Maulida (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
Use of media concept map with ADLX based learning design integrated on biotechnology materials to improve learning outcomes of students class X SMA IT Ummul Quro Bogor semester even academic year 2023-2024”. Class action research report (PTK), Ummul Quro Senior High School Integrated Islamic Bogor, May 2024. The purpose of this research is to know the use of the media concept maps with the design of based learning is to be integrated in biotechnology material to increase the results of learning the class of X. This study was conducted in Senoir High School Integrated Islamic Ummul Quro Bogor in the academic year 2023 / 2024. The subject of this research is a student of Class X-3 ikhwan which totaled 32 students. This research is a qualitative research using research methods class action (PTK) as many as two cycles. Each cycle consists of four phases, such as: 1) Planning Actions, 2) Implementation of Actions, 3) The Observation of Action 4) Reflection. The results of this study show that the use of concept map media with integrated ADLX based learning design on biotechnology materials can improve the learning outcomes of class x-3 biology with a percentage of the merit of the learning goal criteria (KKTP) of 46.88% on cycle I to 81.25% on cycle II. Students can play an active in learning, constructing new knowledge and exploiting learning material through the creation of concept maps so that learning becomes deep and meaningful. This can be seen from observation of the educational activity of the participants who experienced an increase from 3.5 on the cycle I to 3.9 on the cycle II.